Commodity Recommendation Model Integrating User Psychological Data Analysis - Xu, Yan; Cui, Wantian (Frontiers in Psychology, 2022)
E-commerce recommendation plays an irreplaceable role in alleviating product information overload and improving consumers' personalized experience and sales conversion rate. According to the idea of recommendation, e-commerce recommendation can be divided into two types: recommendation based on correlation and recommendation based on causality. The former, such as collaborative filtering and other recommendation methods, is highly dependent on data; the latter, such as product recommendation based on consumer psychology, has great superiority in new product recommendation due to the introduction of such domain knowledge as consumer psychology in the recommendation. In this paper, we select three representative consumer psychologies of "consumer motivation", "consumer attitude" and "consumer interest" to explore the recommendation of products with multiple consumer psychologies. On the one hand, according to the theory of consumption psychology and the need of e-commerce recommendation, some product-store attributes are selected as attribute variables. A comprehensive comparison and analysis of the patterns presented by multiple consumer psychology in product recommendations is conducted, and the patterns of multiple consumer psychology product recommendations are analyzed from two perspectives: recommendation stability and recommendation result patterns, respectively, and the reasons for them are analyzed. It is clear that the recommendation method based on dual consumption psychology and triple consumption psychology can also effectively achieve product recommendation. In this paper, we compare and analyze the difference in recommendation accuracy between single consumption psychology, dual consumption psychology and triple consumption psychology, and find that compared with single consumption psychology, product recommendation based on dual consumption psychology and triple consumption psychology can basically improve the accuracy of product recommendation, and the accuracy of dual consumption psychology is generally higher than that of triple consumption psychology, among which the accuracy of product recommendation based on dual consumption motivation-attitude psychology is the highest.